European Registry on Helicobacter pylori Management (Hp-EuReg): Most relevant results for clinical practice - Nyssen, Olga P.; Moreira, Leticia; García-Morales, Natalia; Cano-Català, Anna; Puig, Ignasi; Mégraud, Francis; O’Morain, Colm; Gisbert, Javier P. (Frontiers in Gastroenterology, 2022)
BACKGROUND: The best approach for Helicobacter pylori (H. pylori) eradication remains unclear; therefore, the most effective management strategies for adult patients need to be identified to ensure clinical practice is aligned with the best standard of care. Our aim was to perform a review of research studies from the European Registry on H. pylori Management (Hp-EuReg) by synthesising the most clinically relevant information from each published manuscript. METHODS: All research studies published between 2013 and 2022, evaluating any information related to H. pylori infection management within the Hp-EuReg, a long-term Registry of routine clinical practice by gastroenterologists in Europe, were included in the review. RESULTS: Overall, 25 studies have been published to date, where 11 evaluated the overall European data and the remaining were performed locally among the 28 participating countries. Eighteen studies evaluated the effectiveness of first- and/or second-line treatment, where: one focused on penicillin allergic patients, six on specific treatment schemes, one evaluated the role of statins as a concomitant drug when combined with the eradication therapy, one assessed the adverse event profile of treatments, one other evaluated the bacterial antibiotic resistance trends, and a last one reported on the common mistakes in the management of H. pylori infection in routine clinical practice in Europe. CONCLUSION: The Hp-EuReg had a major influence on the routine clinical practice of European gastroenterologists, improving H. pylori eradication treatment success, allowing to make recommendations in line with the current consensus guidelines and potentially serving as a model for other diseases.